2018
DOI: 10.1536/ihj.17-227
|View full text |Cite
|
Sign up to set email alerts
|

Transcatheter Retrieval of Embolized Atrial Septal Defect Occluder Device by Waist Capture Technique

Abstract: SummaryThis case study describes the successful percutaneous transcatheter retrieval of an embolized Amplatzer occluder device using the "waist capture technique" in a patient with an atrial septal defect. This technique allowed for stability of the Amplatzer device, compression of the atrial discs for easier removal, prevention of further embolization, and minimal injury to vasculature during device retrieval. This novel and effective technique can be used safely for the retrieval of Amplatzer devices in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…Next, we searched the literature and found that it is similar to loop snares and other advanced techniques. 4,5,15) Compared with previously reported techniques, our technique has more advantages. Firstly, the loop snare technique reported by Lisa, et al 16) used a 16-F sheath to remove the filter tip.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Next, we searched the literature and found that it is similar to loop snares and other advanced techniques. 4,5,15) Compared with previously reported techniques, our technique has more advantages. Firstly, the loop snare technique reported by Lisa, et al 16) used a 16-F sheath to remove the filter tip.…”
Section: Discussionmentioning
confidence: 95%
“…There are a wide variety of techniques which have been used to remove filters that could not be retrieved by conventional methods. [4][5][6][7][8] Among them, one of the most efficient and simplest ways is the loop snare technique. We further modified this method to make it easier to retrieve the filters.…”
mentioning
confidence: 99%
“…Based on our experience in vitro, it was harder to retrieve a device in the “locked state” into a same size delivery sheath, as compared to that in the “unlocked state.” Therefore, we suggest the use of a sheath larger than the initial delivery sheath to retrieve the embolized device. Moreover, since the marks on the device enable the identification of the position of the waist and the tip of the left disc, the “Waist Capture Technique” with a looped wire or a snare to capture the waist of the device might be feasible for device retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…Cihazın biopsi kateterleri yada Amplatz GooseNeck® Snare( Abbott Medical, USA) ile geri alınması söz konusu olsa da başarısız olunmasında cerrahi güvenli bir seçenektir. Hatta, Her et al (11). da venöz sisteme embolize olan cihazın farklı bir teknik olarak cihazın bel kısmında yakalanarak çıkarılmasını sunmuşlardır.…”
Section: Discussionunclassified